Assessment of the bioaccumulation pattern of Pb, Cd, Cr and Hg in edible fishes of East kolkata Wetlands, India - Dutta, Joystu; Zaman, Sufia; Thakur, Tarun Kumar; Kaushik, Sandeep; Mitra, Abhijit; Singh, Poonam; Kumar, Ravinder; Tan, Ali Kee Zuan; Samdani, Mohammad Shahzad; Alharbi, Sulaiman Ali; Datta, Rahul (Elsevier, 2021)
Waste water fed pisciculture is nowadays a common feature in aquaculture belts across the globe. East Kolkata Wetlands (EKW) a nature’s wonder where waste water fed natural aquaculture beltis is active for more than 70 years now and is efficiently operating as a natural waste management system. The peri urban wetland is also a site of international importance and is listed in Ramsar. Field and lab-based investigations were carried out using three commonly edible carp variety of fishes such as Rohu (Labeorohita), Catla (Catlacatla) and Nile Tilapia (Oreochromisniloticus) collected from ponds (bheries) of the wetland located on the eastern fringes of Kolkata, India. The lab-based analysis revealed the presence of toxic metals such as Cr, Pb, Cd and Hg in the samples with the seasonal order of accumulation being monsoon > post-monsoon > winter > pre-monsoon in the successive years of 2016, 2017 and 2018. Bio-accumulation of toxic heavy metals in fishes follows the order Tilapia > Rohu > Catla where as the bioaccumulation pattern of toxic metals shows the trend Pb > Cd > Cr > Hg across all the seasons and years. The ambient media was also investigated to understand in detail the bioaccumulation pattern at different trophic levels of the ecosystem. Water and sediments were analyzed to evaluate the contamination of toxic heavy metals from point and non-point sources. Current study shows the observed bioaccumulation pattern of the toxic heavy metals in one of the fragile ecosystems that raises an important question of environmental safety in the food we intake on daily basis.